2004
DOI: 10.1111/j.1365-2672.2004.02243.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of microcosms to determine persistence of Escherichia coli in recreational coastal water and sediment and validation with in situ measurements

Abstract: Aims: To determine the persistence of the faecal indicator organism Escherichia coli in recreational coastal water and sediment using laboratory-based microcosms and validation with in situ measurements. Methods and Results: Intact sediment cores were taken from three distinct coastal sites. Overlying estuarine water was inoculated with known concentrations of E. coli and decay rates from both overlying water and sediment were determined following enumeration by the membrane filtration method at fixed time int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
135
5
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(157 citation statements)
references
References 25 publications
15
135
5
2
Order By: Relevance
“…Water temperature increased gradually over the sampling period from 13 to 29 xC in SN and from 8 to 25 xC in OLD. E. coli survival was shown to be negatively linked to temperature ranges between 10 and 30 xC in various environments (Faust et al, 1975;Servais et al, 1985;Craig et al, 2004). However no evidence in the present work suggests that an increase in water temperature was linked to lower E. coli concentrations at sampling time, or beneficially influenced persistence during the holding period (Table 3).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Water temperature increased gradually over the sampling period from 13 to 29 xC in SN and from 8 to 25 xC in OLD. E. coli survival was shown to be negatively linked to temperature ranges between 10 and 30 xC in various environments (Faust et al, 1975;Servais et al, 1985;Craig et al, 2004). However no evidence in the present work suggests that an increase in water temperature was linked to lower E. coli concentrations at sampling time, or beneficially influenced persistence during the holding period (Table 3).…”
Section: Discussioncontrasting
confidence: 54%
“…Particles can also represent ecological shelters against grazing pressure (Brettar and Ho¨fle, 1992). Suspended solids such as sand, clay mineral or organic matter were also demonstrated to provide protection against UV light by limiting the depth of light penetration in the water column in estuarine or freshwater environments (Marshall, 1968;Craig et al, 2004;Beversdorf et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is an effect of salinity on the survival of enteric bacteria, although yet it is less significant than expected. Craig et al (2004) reported that coliform bacteria have little tolerance to high salinity, and concluded that the detection of coliforms in the environment is indicative of a steady discharge of fecal material. Kolm et al (2002) found no correlation between pH and coliform MPN in water, and Scott et al (2003) found no correlation of temperature and pH with water contamination levels.…”
Section: Resultsmentioning
confidence: 99%
“…The high survival of these organisms in sediment may be due to the protection offered by the sediment from protozoan predation (Davies and Bavor 2000), availability of nutrients (Craig et al 2004) and by substratum for adherence (Davies et al 1995). A greater difference between the densities of bacterial population in the presence of protozoan predators compared to those in their absence was observed for E. coli, V. parahaemolyticus and S. paratyphi in water and sediment.…”
Section: Survival Of Indicator and Pathogenic Bacteria In Water And Smentioning
confidence: 99%